study guide to accompany psychology - Straub, Richard O.; Myers, David G (New York : Worth Publishers, 2010)
A study guide that helps students to understand the material in psychology. It features chapter that include self-test and exercises, chapter reviews and overviews, and objectives.
Keywords: psychology -- Problems, exercises, etc; Psychology -- Study guides -- Examinations